Improving Student’s Positive Responses to Schools Rules - Rianawati, Rianawati; Yusuf, Muhammad; Herlambang, Saifuddin; Ramli, Yapandi (TARBIYA: Journal of Education in Muslim Society, 2020)
AbstractSchools discipline aims to keep the peace and the good implementation process of learning in school. Besides, the habituation of student’s discipline is very vital that the students get used to obeying the rules, accustomed to being an orderly, neat, and organized in a range so that students are comfortable to achieve a better future, for themselves, society, nation, and state. However, many students in the school who are less or even break on school discipline, so the result is a deviation and dependency character (moral) that occur in society, especially in young children (school age). This research approach is a qualitative approach with descriptive methods analytic types of case studies. The location of this research is Madrasah Aliyah Negeri 1 (MAN) Mempawah. Data collection techniques are observation, interviews, and document analysis. While the data analysis technique is a reduction, display, and data verification. The results reveal that the internalization of disciplinary character in MAN 1 Mempawah conducted seriously through the process of values transformation, transaction, and trans internalization as well as through various extracurricular activities and disciplinary culture in schools. AbstrakDisiplin sekolah bertujuan untuk menjaga ketentraman dan terlaksananya proses pembelajaran di sekolah dengan baik. Selain itu pembiasaan kedisiplinan siswa sangat vital, agar siswa terbiasa taat pada aturan, terbiasa tertib, rapi, dan teratur dalam jangkauan sehingga siswa nyaman untuk meraih masa depan yang lebih baik, bagi dirinya, masyarakat, bangsa. dan negara bagian. Namun banyak siswa di sekolah yang kurang atau bahkan melanggar disiplin sekolah, sehingga mengakibatkan terjadinya penyimpangan dan ketergantungan karakter (moral) yang terjadi di masyarakat terutama pada anak usia sekolah (usia sekolah). Pendekatan penelitian ini adalah pendekatan kualitatif dengan metode deskriptif analitik jenis studi kasus. Lokasi penelitian ini adalah Madrasah Aliyah 1 (MAN) Kabupaten Mempawah. Teknik pengumpulan data adalah observasi, wawancara, dan analisis dokumen. Sedangkan teknik analisis datanya adalah reduksi, penyajian, dan verifikasi data. Hasil penelitian menunjukkan bahwa internalisasi karakter disiplin di MAN 1 Mempawah dilakukan secara serius melalui proses transformasi nilai, transaksi, dan transinternalisasi serta melalui berbagai kegiatan ekstrakurikuler dan budaya disiplin di sekolah.How to Cite: Rianawati., Yusuf, M., Herlambang, S., Ramli, Y. (2020). Improving Student’s Positive Responses to Schools Rules. TARBIYA: Journal of Education in Muslim Society, 7 (1), 119-132-118. doi:10.15408/tjems.v7i1.15038.